Respuesta :
Answer:
F = (μs mg)/(cosθ + μs sinθ)
Explanation:
Hi!
In order to find F in terms of m, g, θ and μs we need to find N in terms of the same variables.
This can be accomplished by solving the second equation (vertical components) for N:
Fsinθ+N−mg=0
N = mg - Fsinθ
Now we can replace the value of N in the first equation (horizontal components):
Fcosθ − μsN=0
Fcosθ − μs(mg - Fsinθ) = 0
Fcosθ − μs mg + μs Fsinθ = 0
F (cosθ + μs sinθ) = μs mg
Therefore:
F = (μs mg)/(cosθ + μs sinθ)
Hope this helps!
Answer:
[tex]F= \frac{us*m*g}{cos (\alpha) + us * sen(\alpha ) }[/tex]
Explanation:
[tex]F*cos (\alpha )- us*N=0\\F*sen(\alpha )+N-m*g=0\\N=m*g-Fsen(\alpha )\\F*cos (\alpha )- us*(m*g-Fsen(\alpha ))=0\\F*cos (\alpha )- us*m*g+us*Fsen(\alpha )=0\\F*(cos (\alpha )+ us*sen (\alpha ))=us*m*g\\F=\frac{us*m*g}{cos (\alpha )+ us*sen (\alpha )}[/tex]